Labor Management Procedures (LMP)-AICCRA Additional Financing (P181150) - International Center for Tropical Agriculture (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This Labor Management Procedures (LMP) has been updated for the Additional Financing (AF) of the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project (P181150). This updated LMP will be used for the Parent Project (P173398) and the AF (P181150). The International Centre for Tropical Agriculture (CIAT) has revised this LMP to guide mitigation and response to key labor and Occupational Health and Safety (OHS) risks envisaged on AICCRA-AF. This LMP will constitute a guiding instrument for management of labor and working conditions for CIAT and all other grant partners implementing activities on AICCRA-AF. Based on this LMP, individual grant partners may be required to prepare separate occupational health and safety plans proportionate to their project risks to mitigate and respond to OHS risks. CIAT has prepared this LMP to set the basis for providing a clear understanding to grantees and project workers on what is required on any specific labor issue. The purpose of the LMP is to facilitate the identification of different types of workers that are likely to be involved in the project and set out the ways in which those workers will be managed in accordance with the requirements of national laws and the objectives of the World Bank Environmental and Social Standard 2: Labor and Working Conditions (ESS-2) and Standard 4: Community Health and Safety (ESS-4) of the Environmental and Social Framework (ESF).